2013
DOI: 10.1016/j.ntt.2013.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Maternal serum persistent organic pollutants in the Finnish Prenatal Study of Autism: A pilot study

Abstract: Recent research emphasizes the contribution of environmental as well as genetic factors to the etiology of autism but studies testing associations between chemical exposures and autism have been limited. Prenatal exposure to persistent organic pollutants (POPs) has previously been associated with decrements in cognitive and developmental performance. We conducted a pilot study in the Finnish Prenatal Study of Autism (FiPS-A). Seventy-five cases with autism and 75 controls matched on sex, birth year, urbanizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
93
0
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(99 citation statements)
references
References 39 publications
3
93
0
3
Order By: Relevance
“…Because the hypothalamus is critically important for the regulation of mood and emotion, as well as sociality (Engel, Miodovnik et al 2010, Hoffman, Webster et al 2010, Miodovnik, Engel et al 2011, Eskenazi, Chevrier et al 2013), the neural outcomes reviewed here are consistent with and supportive of epidemiological data in children associating BPA and PCBs with ASD, ADHD, and anxiety disorders (Eubig, Aguiar et al 2010, Sagiv, Thurston et al 2010, Braun, Kalkbrenner et al 2011, Cheslack-Postava, Rantakokko et al 2013). Interestingly, no immune related endpoints have been investigated to date in sub-adult animals, even though some immune cells like microglia (Wood 2011, Wu, Tan et al 2013) and neutrophils (Molero, Garcia-Duran et al 2002, Shindo, Moore et al 2013) have been found to express estrogen receptors, impact sexually dimorphic development (O’Malley, Liston et al 2011) and the immune system is reciprocally influenced by the hypothalamus.…”
Section: Resultssupporting
confidence: 80%
“…Because the hypothalamus is critically important for the regulation of mood and emotion, as well as sociality (Engel, Miodovnik et al 2010, Hoffman, Webster et al 2010, Miodovnik, Engel et al 2011, Eskenazi, Chevrier et al 2013), the neural outcomes reviewed here are consistent with and supportive of epidemiological data in children associating BPA and PCBs with ASD, ADHD, and anxiety disorders (Eubig, Aguiar et al 2010, Sagiv, Thurston et al 2010, Braun, Kalkbrenner et al 2011, Cheslack-Postava, Rantakokko et al 2013). Interestingly, no immune related endpoints have been investigated to date in sub-adult animals, even though some immune cells like microglia (Wood 2011, Wu, Tan et al 2013) and neutrophils (Molero, Garcia-Duran et al 2002, Shindo, Moore et al 2013) have been found to express estrogen receptors, impact sexually dimorphic development (O’Malley, Liston et al 2011) and the immune system is reciprocally influenced by the hypothalamus.…”
Section: Resultssupporting
confidence: 80%
“…We hypothesize that one of the major reasons for the alarming rise in autism and autism spectrum disorder is the rise in use of fragrances 2 . It should be noted that autism used to be a relatively rare diseases at the turn of the 20th century [2][3][4][5][6][22][23][24] , but it has now been found that 1 out 88 children is suffering from ASD; again, this may be an underestimate. Since a neonate's brain is still developing after birth, we should expect a rise in other neurological but related conditions (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Since a neonate's brain is still developing after birth, we should expect a rise in other neurological but related conditions (e.g. attention de icit hyperactive disorder [ADHD], regressive autism; for example, a child is born normal but begins to show signs of autism after 18 months or later) [21][22][23][24] . ASD is a developmental condition characterized by de icits in social interaction, verbal and nonverbal communication and obsessive/stereotyped patterns of behaviour.…”
Section: Discussionmentioning
confidence: 99%
“…Five studies in the first category (a) utilized biomarkers of toxicant exposure 17, 18, 19, 20, 21 to create dichotomous toxicant exposure groups and then prospectively investigated whether these exposure groups were associated with ASD development later in life. As these studies were not primarily concerned with the relationship between these biomarkers and ASD, these studies were placed into category (a) instead of (b).…”
Section: Methodsmentioning
confidence: 99%